2009
DOI: 10.1542/peds.2007-3618
|View full text |Cite
|
Sign up to set email alerts
|

Latent Tuberculosis Diagnosis in Children by Using the QuantiFERON-TB Gold In-Tube Test

Abstract: The QuantiFERON-TB Gold In-Tube test is a specific test for M tuberculosis exposure in children, with performance characteristics similar to those for adults residing in regions with low levels of endemic disease. Concerns about test sensitivity, especially for children <2 years of age, will require additional prospective long-term evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(67 citation statements)
references
References 20 publications
3
56
0
8
Order By: Relevance
“…As regards the indeterminate results, a significantly lower IFN-γ release in response to mitogen (positive control) has been described in young children tested with QFT-IT, suggesting an agedependent response. 47,50 As for T-SPOT.TB, it does not seem to be related to age, 17 except in the first weeks of life. 51 However, Nicol et al 48 reported a decline in positive T-SPOT.TB results in children less than 1 year of age, whereas TST results were unaffected.…”
Section: Paediatric Populationmentioning
confidence: 91%
See 1 more Smart Citation
“…As regards the indeterminate results, a significantly lower IFN-γ release in response to mitogen (positive control) has been described in young children tested with QFT-IT, suggesting an agedependent response. 47,50 As for T-SPOT.TB, it does not seem to be related to age, 17 except in the first weeks of life. 51 However, Nicol et al 48 reported a decline in positive T-SPOT.TB results in children less than 1 year of age, whereas TST results were unaffected.…”
Section: Paediatric Populationmentioning
confidence: 91%
“…4,7 Discordant results between these tests and TST are frequently found. 7,[45][46][47][48] In a study conducted in Barcelona (Spain), 7 among BCG-unvaccinated children, 60% and 57% of those with positive TST had negative QF-IT and T-SPOT.TB respectively. Latorre et al 49 reported that 48% of children with TST positive and negative T-SPOT.TB had sensitized T cells against Mycobacterium avium sensitins.…”
Section: Paediatric Populationmentioning
confidence: 99%
“…In fact, this is supported by previous work showing that in closely similar events, no or very few infants were infected). [3][4][5][6] A third aspect that is surprising and not in agreement with the possibility of an ongoing sequential transmission from a single source (nurse) to newborns in a nursery is the observation that there was one single case of TB disease among exposed newborns, compared to an estimated rate of infections of 9% occurring based on QFT-IT alone. Indeed, a somewhat higher rate of disease occurrence would be expected in newborns with immature immune system.…”
Section: Discussionmentioning
confidence: 99%
“…This preference stems from the fact that TST obtains a stronger immunological response, as it stimulates central memory cells over a longer incubation time, while QFT responses result from effector cells in peripheral blood. In addition, the Th1 system, that produces interferon-gamma, is immature in children while the immune response of the Th2 system (interleukin 4, IFN-gamma, tumour necrosis factor alpha, interleukin 10, interleukin 12, and granulocyte colony-stimulating factor) is active and is more likely detected by TST (19,36). On the other hand, several studies suggest that at higher levels of exposure to TB, the proportion of children with positive results in both IGRAs is higher, independent of the BCG status (11,19,36).…”
Section: Igra In Childrenmentioning
confidence: 99%